Identification of a Type IV-A CRISPR-Cas System Located Exclusively on IncHI1B/IncFIB Plasmids in Enterobacteriaceae - Newire, Enas; Aydin, Alp; Juma, Samina; Enne, Virve I.; Roberts, Adam P. (Frontiers in Microbiology, 2020)
Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) are diverse immune systems found in many prokaryotic genomes that target invading foreign DNA such as bacteriophage and plasmids. There are multiple types of CRISPR with arguably the most enigmatic being Type IV. During an investigation of CRISPR carriage in clinical, multi-drug resistant, Klebsiella pneumoniae, an unusual Type IV-A CRISPR-Cas system which was detected on plasmids from two K. pneumoniae isolates from Egypt (isolated in 2002-2003) and a single K. pneumoniae isolate from the UK (isolated in 2017). Sequence analysis of all other genomes available in GenBank revealed that this CRISPR-Cas system was present on 28 other plasmids from various Enterobacteriaceae hosts and was never found on a bacterial chromosome. This system is exclusively located on IncHI1B/ IncFIB plasmids and is associated with multiple putative transposable elements. Expression of the cas loci was confirmed in the available clinical isolates by RT-PCR. In all cases, the CRISPR-Cas system has a single CRISPR array (CRISPR1) upstream of the cas loci which has several, conserved, spacers which, amongst things, match regions within conjugal transfer genes of IncFIIK/ IncFIB(K) plasmids. Our results reveal a variant of Type IV-A CRISPR-Cas system exclusively located on IncHI1B/ IncFIB plasmids in Enterobacteriaceae that is likely to be able to target IncFIIK/ IncFIB(K) plasmids presumably facilitating intracellular, inter-plasmid competition.